The Impact Of Strategic Human Resources Orientation On Creative Performance - Soulaf Abdalqadir Hameed; Imen Mzid (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this study is to identify the impact of the strategic orientation of human resources in its dimensions (control-oriented human resources strategy, commitment-oriented human resources strategy) on the creative performance in its dimensions (problem identification, information search, idea generation, idea enhancement) of academic leaders at the University of Maysan in Iraq? The study sample consisted of (350) leaders of the University of Maysan and (323) were retrieved. The questionnaire was used as a tool for collecting data and the questionnaire consisted of (32) questions distributed over the dimensions of the study.The study reached the most important results: the existence of a positive impact of the strategic orientation of human resources in terms of (control-oriented human resources strategy, commitment-oriented human resources strategy) on creative performance in its combined dimensions.